Neverwhere a novel - Gaiman, Neil (New York William Morrow, 2016)
After he helps a stranger on a London sidewalk, Richard Mayhew discovers an alternate city beneath London, and must fight to survive if he is to return to the London he knew.
Includes reading group guide.
"Author's preferred text."--Title page.
Keywords: Underground homeless persons -- Fiction; Underground areas -- Fiction; Businessmen -- Fiction; Subways -- Fiction; London (England) -- Fiction; Fantasy fiction; Horror fiction